Ship or Sheep - Baker, Ann, ....- (Cambridge : Cambridge University Press, 2006)
Ship or Sheep? Third edition helps learners make the distinction between similar sounds and ensure they are understood. This new edition of Ship or Sheep?, an accessible intermediate-level pronunciation course in full colour for students of English, provides systematic practice of English pronunciation, with an emphasis on minimal pairs, through a wide variety of interesting exercises and activities. The course is suitable for classroom use or for self-study.
Keywords: Pronunciation Course